2010
DOI: 10.1097/iae.0b013e3181cd4894
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab (Lucentis) for Branch Retinal Vein Occlusion-Induced Macular Edema

Abstract: Individualized repeated intravitreal injections of ranibizumab showed promising short-term results in visual acuity improvement and decrease in CFT in patients with macular edema associated with branch retinal vein occlusion. Further studies are needed to prove the long-term effect of ranibizumab treatment on patients with branch retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
2
10
0
6
Order By: Relevance
“…Changes in thickness and shape of the central segment of the retina in occlusive processes in the central retinal vein and its tributaries are described in other studies that address this issue. (9)(10)(11)(12) This paper describes a 30% increase in average thickness of the macular area of the retina to 386.97 ± 16.26 microns with the highest index in the center corresponding approximately to the results presented by other authors with a similar index of 416 microns at average indices of the central part, and a thickness from 552 microns to 150 ± 668.18 ± 245.58 microns. (9) According to the authors of the paper, the changes in the macula in the retina vein thrombosis affect the outer plexiform layer, the inner nuclear layer and the retinal nerve fiber layer with the internal limiting membrane.…”
Section: Discussionsupporting
confidence: 59%
“…Changes in thickness and shape of the central segment of the retina in occlusive processes in the central retinal vein and its tributaries are described in other studies that address this issue. (9)(10)(11)(12) This paper describes a 30% increase in average thickness of the macular area of the retina to 386.97 ± 16.26 microns with the highest index in the center corresponding approximately to the results presented by other authors with a similar index of 416 microns at average indices of the central part, and a thickness from 552 microns to 150 ± 668.18 ± 245.58 microns. (9) According to the authors of the paper, the changes in the macula in the retina vein thrombosis affect the outer plexiform layer, the inner nuclear layer and the retinal nerve fiber layer with the internal limiting membrane.…”
Section: Discussionsupporting
confidence: 59%
“…2 ) disturbs the retinal osmohomeostasis and hinders edema resolution. Intravitreally applied anti-VEGF agents are used clinically for treating macular edema secondary to CRVO [14,15] . Bevacizu mab prevents the receptor binding of VEGF, resulting in decreased vascular permeability as a major cause of edema.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of Kir4.1 and aquaporins might result in a disruption of the regular potassium and water transport through glial cells, which may hinder the clearance of edema [1] . In addition to intravitreal steroids, an intravitreal injection of anti-VEGF agents such as bevacizumab (Avastin) and ranibizumab (Lucentis) was shown to be efficient in reducing retinal edema due to CRVO [13][14][15] . Because bevacizumab is a full-length humanized monoclonal IgG antibody that binds to the moiety of VEGF responsible for receptor binding, it is assumed that it preferentially inhibits the action of VEGF at the level of target cells.…”
Section: Effect Of Intravitreal Anti-vascular Endothelialmentioning
confidence: 99%
“…At the 6th month of follow-up, mean logMAR visual acuity reached 0.41 ± 0.06. In a previous study, Rouvas et al (20) reported that baseline logMAR visual acuity improved from 0.74 ± 0.28 to 0.48 ± 0.3. Similarly, Ahn et al (31) reported an improvement from 0.61 ± 0.35 logMAR to 0.35 ± 0.30 logMAR.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, these studies did not address the issue of the ischemic or nonischemic nature of the retinal perfusion. Moreover, despite promising results with different dose regimens for bevacizumab injections, clinical trials for intravitreal ranibizumab injections in BRVO are very limited (15)(16)(17)(18)(19)(20)(21). We aimed to assess the efficacy of pro re nata (PRN) intravitreal ranibizumab injection from the start in the treatment of ME in patients with ischemic or nonischemic BRVO.…”
Section: Introductionmentioning
confidence: 99%